The Use of the Health of the Nation Outcome Scales for Assessing Functional Change in Treatment Outcome Monitoring of Patients with Chronic Schizophrenia - Egger, Stephan T.; Vetter, Stefan; Weniger, Godehard; Vandeleur, Caroline; Seifritz, Erich; Müller, Mario (Frontiers in Public Health, 2016)
Background: Schizophrenia is a severe mental disorder that is characterized by symptomatic severity but also by high levels of functional impairment. An evaluation of clinical outcome in treatment of schizophrenia should therefore target not only assessing symptom change but also alterations in functioning. This study aimed to investigate whether there is an agreement between functional and symptom-based outcomes in a clinical sample of admissions with chronic forms of schizophrenia. Methods: A full 3-year cohort of consecutive inpatient admissions for schizophrenia (N=205) was clinically rated with the Positive And Negative Symptom Scale (PANSS) and the Health of the Nation Outcome Scales (HoNOS) as measures of functioning at the time of admission and discharge. The sample was stratified twofold: First, according to the degree of PANSS symptom improvement during treatment with the sample being divided into three treatment response groups: Non-response (NR), low-response (LR) and high-response (HR). Second, achievement of remission was defined using the Remission in Schizophrenia Working Group criteria (RSWGcr) based on selected PANSS symptoms. Repeated measures analyses were used to compare the change of HoNOS-scores over time across groups. Results: More than a half of all admissions achieved a symptom reduction of at least 20% during treatment and around one quarter achieved remission at discharge. Similarly, HoNOS-scores improved significantly between admission and discharge. Interaction analyses indicated higher functional improvements to be associated with increasing levels of treatment response. Conclusion: Functional improvement in individuals treated for schizophrenia was linked to a better clinical outcome, which implies a functional association. Thus, improvement of functioning represents an important therapeutic target in the treatment of schizophrenia.